Irradiation processing of immiscible PP/EOC blend: Morphology control and processability modification. Issue 11 (7th October 2020) - Hassan, Fatemeh; Entezam, Mehdi
Abstract: In this study, applying electron beam irradiation method at a relatively low‐irradiation dose (20 kGy) under the air atmosphere to prepare injectable polypropylene (PP)/ethylene‐octene copolymer (EOC) blends with fine morphology and appropriate performance was investigated. For this purpose, an extrusion PP grade with an EOC grade suitable to improve its impact resistance was melting blended. Gel content and rheological measurements revealed long‐chain branching is predominant phenomenon occurring during the irradiation process of EOC. Blend irradiation resulted in changing its melt flow index proper for injection molding. A fine morphology obtained for the unirradiated blend was preserved for the irradiated blend. Moreover, irradiation thermally stabilized the blend morphology. Blends linear viscoelastic behavior discussed by proper rheological models revealed the existence of interfacial interactions and a reduction of the interfacial tension between irradiated blend phases. No significant effect of irradiation on the crystallization characteristics of EOC and the blend was observed. The satisfying impact resistance of the irradiated blend was near to that of the unirradiated blend, although its tensile mechanical properties were less. Abstract :